A Juridical Analysis of Mental Health Regulations and the Rights of Mental Disorder Patients - M.Hasibuan; N.Damanik (The Medical Journal of Hospital Management and Health Law, 2025)
Introduction: Mental health regulations often stand at a complex crossroads between state authority, public safety, and individual liberties. This study examines the legal framework governing mental health to evaluate how effectively current statutes protect the fundamental human rights of patients diagnosed with mental disorders. Methods: Using a normative juridical research method, this study analyzes statutory approaches, conceptual frameworks, and comparative legal literatures concerning mental health rights. Results: The analysis reveals that while formal statutory protections exist on paper, significant legal ambiguities remain regarding involuntary commitment, informed consent, and institutional oversight. These gaps frequently lead to the systemic deprivation of liberty and a lack of legal recourse for vulnerable patients. Discussion: The discussion deepens the literature review by contrasting protective constitutional mandates against discretionary medical powers, highlighting a critical implementation gap where administrative convenience overrides patient autonomy. Systemic stigma embedded within historical legal definitions further complicates the realization of therapeutic justice. Conclusions: This study concludes that existing mental health regulations require immediate, comprehensive harmonization with international human rights standards to ensure robust legal protections. It recommends establishing independent legal advocacy bodies and strict judicial review mechanisms for all involuntary psychiatric interventions.